Analysis of the Dusturiyah System on Community Participation in the 2024 Presidential Election Re-vote (Study at TPS 21, Sei Putih Tengah Village, Medan Petisah District - Rizki Hsb, Nuryolanda; Marpaung, Zaid Alfauza (LEGAL BRIEF, 2025)
This research was motivated by a discrepancy in determining the voter list for the 2024 general election at TPS 21, Sei Putih Tengah Subdistrict, Medan Petisah District. Due to this discrepancy, a revote (PSU) was carried out. The aim of this research is to find out how siyasah dusturiyah analyzes the community's participation in the 2024 presidential election re-voting at TPS 21, Sei Putih Tengah sub-district, Medan Petisah sub-district. This research uses empirical legal (sociological) research methods sourced from primary and secondary data, namely obtained directly from the community and official documents from the KPU, the Election Law, books and literature related to Siyasah Dusturiyah. The research results showed that of the 236 voter lists, only 108 people exercised their voting rights. This reflects a decline in voter participation due to various factors, such as distrust of the election process, political fatigue, or a lack of outreach regarding the importance of repeat voting. From Siyasah Dusturiyah's view, re-voting can strengthen the legitimacy of election results because this process ensures that the election runs are in accordance with the principles of fairness and openness. On the other hand, if re-voting is not carried out transparently, this could actually lead to distrust of election organizers.